2009
DOI: 10.1002/chem.200900100
|View full text |Cite
|
Sign up to set email alerts
|

Silver–Ethene Complexes [Ag(η2‐C2H4)n][Al(ORF)4] with n=1, 2, 3 (RF=Fluorine‐Substituted Group)

Abstract: Compounds including the free or coordinated gas-phase cations [Ag(eta(2)-C(2)H(4))(n)](+) (n = 1-3) were stabilized with very weakly coordinating anions [A](-) (A = Al{OC(CH(3))(CF(3))(2)}(4), n = 1 (1); Al{OC(H)(CF(3))(2)}(4), n = 2 (3); Al{OC(CF(3))(3)}(4), n = 3 (5); {(F(3)C)(3)CO}(3)Al-F-Al{OC(CF(3))(3)}(3), n = 3 (6)). They were prepared by reaction of the respective silver(I) salts with stoichiometric amounts of ethene in CH(2)Cl(2) solution. As a reference we also prepared the isobutene complex [(Me(2)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 111 publications
11
74
1
2
Order By: Relevance
“…A figure of 2 is deposited with the Supporting Information. For the [hfip] À and the [hftp] À anions, the tetraalkylammonium salts are the second examples of really ionic solid-state structures with isolated anions and cations, [41] while all the other species containing these anions, contain molecular structures with coordinated anions, for example, [(P 4 S 3 )AgA], [31,32] [(P 4 )AgA], [45] [(L) 2 AgA], [35,46] or [(L)AgA] [35,46] ( [47] and later in more detail by Glasser and Jenkins. [43,48] This concept allows thermodynamic predictions for condensed phases principally via formula unit volumes.…”
Section: Solid-state Structures: For Some Of the [Nr 4 ]mentioning
confidence: 99%
See 1 more Smart Citation
“…A figure of 2 is deposited with the Supporting Information. For the [hfip] À and the [hftp] À anions, the tetraalkylammonium salts are the second examples of really ionic solid-state structures with isolated anions and cations, [41] while all the other species containing these anions, contain molecular structures with coordinated anions, for example, [(P 4 S 3 )AgA], [31,32] [(P 4 )AgA], [45] [(L) 2 AgA], [35,46] or [(L)AgA] [35,46] ( [47] and later in more detail by Glasser and Jenkins. [43,48] This concept allows thermodynamic predictions for condensed phases principally via formula unit volumes.…”
Section: Solid-state Structures: For Some Of the [Nr 4 ]mentioning
confidence: 99%
“…This also holds for a series of silver and copper(I) complexes with very weakly basic ligands, for example, P 4 , [29,30] P 4 S 3 , [31,32] S 8 , [33] P 3 N 3 Cl 6 , [34] or C 2 H 4 . [35,36] Since the starting materials to prepare compounds of the fluorinated aluminates are commercially available (best at P&M Invest Russia; http:// www.fluorine.ru) and the synthesis of the lithium aluminate salts [37][38][39] is a simple high yield procedure that we have performed in scales up to 250 g per batch, [40] it only appeared logical to extend the available substance classes to [NR 4 ] + salts. During the preparation of this manuscript, an independent communication of the electrochemical windows of related compounds appeared.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was suggested, after analyzing atomic population changes upon ligand adsorption on a bare cation versus the cation embedded in a model environment that the unusual catalytic activity of transition-metal exchanged zeolites should be due to the activation of the transition-metal ion by the zeolite framework which functions as a specific ligand. Theoretical studies devoted to the interaction of small ligands with multiple bonds bound by zeolitic sites clearly indicated that the charge flow upon adsorption involves several transfer channels, strongly dependent on a zeolite framework type and a cation position [23,[26][27][28][29][30]. Populations within orbital resolution and devised selection schemes, frequently supported by topological analyses of electron density, were able to discriminate distinct electron transfers for a model metal-ligand bond [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies devoted to the interaction of small ligands with multiple bonds bound by zeolitic sites clearly indicated that the charge flow upon adsorption involves several transfer channels, strongly dependent on a zeolite framework type and a cation position [23,[26][27][28][29][30]. Populations within orbital resolution and devised selection schemes, frequently supported by topological analyses of electron density, were able to discriminate distinct electron transfers for a model metal-ligand bond [23,26,27]. Nevertheless, modern tools serving this purpose are still desirable to get better insight into individual chargetransfer processes between fragments constituting the complex system, within general partition schemes into preselected fragments with arbitrary symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The non-coordinating or at least extremely weakly coordinating anions X meanwhile have included not only a) fully fluorinated groups BF 4 [36].…”
Section: Potential Sources Of [Lau]mentioning
confidence: 99%